Overview on Digital Age in Ravinder Singh’s I Too Had a Love Story and Your Dreams Are Mine Now: Exploring Love and Identity in the Digital Age (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ravinder Singh, an essayist of the Digital Age, is the top of the line writer of his love set of three I Too Had a Love Story, Can Love Happen Twice? what's more, Like It Happened Yesterday. His presentation novel I Too Had a Love Story is focused on a genuine occasion that occurred in his reality. The depiction of the occurrence is a typical one that happens in the lives of thousands of youthful couples who assemble and get tied in a marital bunch through one of the various wedding sites like jeevansaathi. com, shaadi.com, etc. However, the current novel I Too Had a Love Story is the depiction of an unordinary contort in his love adventure which drove him to discover his aptitude as an author. The ebb and flow research paper attempts to introduce how Singh through his unsatisfied love seepages to increase a personality and starts his novel with an extremely important and overflowing line Not every person right now the destiny to value the fullest type of love. Some are brought into the world just to encounter its condensing.